Review on Principal and Applications of Temporal and Spatial Beam Shaping for Ultrafast Pulsed Laser - Jong Hyun Kim; Hae Woon Choi (Photonics)
Ultrafast or ultrashort pulsed lasers have become integral in numerous industrial applications due to their high precision, non-thermal interaction with materials, and ability to induce nonlinear absorption. These characteristics have expanded their use in microfabrication, semiconductor processing, automotive engineering, and biomedical fields. Temporal pulse shaping reduces laser pulse durations, often to shorter timescales than many physical and chemical processes, enabling greater control. Meanwhile, spatial shaping improves efficiency and precision in micro- and nanofabrication and biomedical applications. Advances in optical parametric amplifiers (OPAs) and chirped-pulse amplifiers (CPAs) have allowed for more refined temporal and spatial shaping, ensuring the preservation of high peak power while achieving ultrashort pulse durations. Additionally, spatial light modulators (SLMs) have facilitated sophisticated beam shaping, which, when combined with ultrafast lasers, supports applications like computer-generated holography and nanoscale fabrication. These developments underscore the growing utility and versatility of ultrafast lasers in both research and industrial contexts.